Division of the tropical savanna fire season into early and late dry season burning using MODIS active fires - Tom Eames; Roland Vernooij; Jeremy Russell-Smith; Cameron Yates; Andrew Edwards; Guido R. van der Werf (International Journal of Applied Earth Observations and Geoinformation, 2023)
Tropical savannas and grasslands are the most frequently burned biome in the world, and fire has an important role in sustaining ecosystem processes. Modern management of fires in savannas has roots in traditions stretching back centuries, and nowadays earth observation data is incorporated extensively in fire management practices. In tropical savannas in particular strongly seasonal monsoonal climates allow relatively low severity prescribed burning in the early part of the dry season (EDS) with the goal of preventing more destructive late dry season (LDS) fires. In many regional contexts it is common that a specific, fixed date is used officially to indicate when the window of safe burning has expired and the EDS transitions to the LDS, based on the experience of local or regional fire management authorities. This approach, while practical, neglects inter-annual variability in meteorological conditions and timing of onset of more dangerous fire weather. In this study, we pro-pose a remote sensing-based method for determining when this EDS window expires for five savanna-dominated continental-scale regions. By taking ad- vantage of the fact that conditions allowing night-time burning occur later in the dry season, we use day and night-time active fire detections from the MODerate Resolution Imaging Spectroradiometer (MODIS) instruments to set a flexible date of transition between the EDS and LDS. The vast majority of tropical savannas have very variable (std. dev. ≈ 20–40 days) transition dates, though this is somewhat modulated by fire frequency. Fuel connectivity rather than fuel condition appears to be a strong driving factor behind this variability. We find that especially national parks and protected areas have a high proportion of potentially more severe burning in the LDS, though areas with well-established EDS burning programmes are reducing this impact.